Discovery of triazolopyridinone GS-462808, a late sodium current inhibitor (Late INai) of the cardiac Nav1.5 channel with improved efficacy and potency relative to ranolazine. Issue 13 (1st July 2016) - Koltun, Dmitry O.; Parkhill, Eric Q.; Elzein, Elfatih; Kobayashi, Tetsuya; Jiang, Robert H.; Li, Xiaofen; Perry, Thao D.; Avila, Belem; Wang, Wei-Qun; Hirakawa, Ryoko; Smith-Maxwell, Catherine; Wu, Lin; et al.
Graphical abstract: Abstract: Previously we disclosed the discovery of potent Late INa current inhibitor2 (GS-458967, IC50 of 333 nM) that has a good separation of late versus peak Nav 1.5 current, but did not have a favorable CNS safety window due to high brain penetration (3-fold higher partitioning into brain vs plasma) coupled with potent inhibition of brain sodium channel isoforms (Nav 1.1, 1.2, 1.3). We increased the polar surface area from 50 to 84 Å 2 by adding a carbonyl to the core and an oxadiazole ring resulting in3 GS-462808 that had lower brain penetration and serendipitously lower activity at the brain isoforms. Compound3 has an improved CNS window (>20 rat and dog) relative to2, and improved anti-ischemic potency relative to ranolazine. The development of3 was not pursued due to liver lesions in 7 day rat toxicology studies.